Pembinaan Kepada Anak Remaja PPA ID 0622 Takong Tentang Pengajaran Siapa Yesus dan Amanat Agung Tuhan Yesus - Sinaga, Rajokiaman; Warni, Rosma (Society : Jurnal Pengabdian Masyarakat, 2023)
Teaching about who Jesus is and the Great Commission of the Lord Jesus is a part of Christian life that cannot be ignored. Just like the Lord Jesus always gave teachings about who Jesus was and his purpose for coming to this world. It is very important for youth as the church generation to understand and have an understanding of who Jesus really is and the Great Commission of the Lord Jesus. In this regard, this Community Service (PkM) activity journal focuses on fostering teaching about Who Jesus is and the great Message of the Lord Jesus to teenagers PPA ID 0622 Takong. This activity is a means to equip the correct understanding for teenagers PPA ID 0622 Takong. So that teenagers can have a correct understanding and can apply it in everyday life.